Examining the Risk of Recurring Use of Force Incidents Among Newly Hired Police Officers - Gullion, Christi (Crime & delinquency, 2023)
Police force, though rare, has profound implications for citizens and officers involved and the community-at-large. It is vital for police agencies to review officer use of force, identify potential misconduct, and reduce repeated officer misconduct. Yet, little is known about what predicts subsequent uses of force and temporal distance between uses of force. The current study employs use of force data from a large, metropolitan police agency in the southwestern United States to examine the likelihood and timing between repeated uses of force. Results indicate officers may be affected by police-citizen encounters, as the likelihood of a subsequent use of force was reduced when their initial use of force occurred in neighborhoods with higher minority composition and the time to a subsequent use of force increased when their initial use of force resulted in citizen injury. For officers with a subsequent use of force, more than half had their next use of force within 3 months of their initial use of force, and 93% did so within a year of their initial use of force. Policy implications include enhanced supervision for new officers and accountability tools such as internal affairs and early intervention (EI) systems.